2015
DOI: 10.1007/s11481-015-9643-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Epigenetic Regulation of Pro-Inflammatory Cytokines, Interleukin-12 and Interferon Gamma, in Peripheral Blood Mononuclear Cells from PTSD Patients

Abstract: While Post Traumatic Stress Disorder (PTSD) is associated with immune dysfunction, the underlying mechanisms remain unclear. Studies suggest a role for involvement of epigenetic mechanisms and microRNAs (miRNAs). Here, we examined genome-wide histone and DNA methylation in the peripheral blood mononuclear cells (PBMCs) in PTSD. We noted significant differences in histone H3 trimethylation at K4, K9, K27 and K36 sites in PTSD when compared to control. While overall DNA methylation level did not differ significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 47 publications
(56 reference statements)
5
65
0
2
Order By: Relevance
“…While regular cortisol production serves a protective function against excessive inflammation (Silverman, Pearce, Biron, & Miller, 2005), exposure to excessive stress or trauma can result in dysregulated HPA axis function (Charmandari, Tsigos, & Chrousos, 2005;Elenkov, Iezzoni, Daly, Harris, & Chrousos, 2005). A recent study has found evidence suggesting epigenetic mechanisms of the histone and DNA methylation regulation of genes involved in proinflammatory cytokine expression is upregulated in PTSD subjects compared to controls (Bam et al, 2016). Epigenetic mechanisms have also been linked to brainderived neurotrophic factor (BDNF) expression involved in the extinction of conditioned fear (Blouin, Sillivan, Joseph, & Miller, 2016;Bredy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While regular cortisol production serves a protective function against excessive inflammation (Silverman, Pearce, Biron, & Miller, 2005), exposure to excessive stress or trauma can result in dysregulated HPA axis function (Charmandari, Tsigos, & Chrousos, 2005;Elenkov, Iezzoni, Daly, Harris, & Chrousos, 2005). A recent study has found evidence suggesting epigenetic mechanisms of the histone and DNA methylation regulation of genes involved in proinflammatory cytokine expression is upregulated in PTSD subjects compared to controls (Bam et al, 2016). Epigenetic mechanisms have also been linked to brainderived neurotrophic factor (BDNF) expression involved in the extinction of conditioned fear (Blouin, Sillivan, Joseph, & Miller, 2016;Bredy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in H3K4 have been reported in humans after prolonged exposure to metal components of particulate matter air pollution (Cantone et al, 2011). While early increases in H3K4 methylation 3 d after exposure to WTC dust are likely linked to acute inflammation, decreases at 21 d are consistent with chronic inflammation (Bam et al, 2016). COX-2 gene expression has been reported to be regulated, in part, by chromatin modifications (Cao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among the six selected miRNAs from mice studies, miR193a-5p was found to be induced by HT consumption in humans. In PBMCs, it was showed very recently that up-regulation of miR-193a-5p could have antiinflammatory effects by decreasing the expression of IL-12 [51].…”
Section: Discussionmentioning
confidence: 99%